Diagnostic yield of FAP-guided positron emission tomography in thyroid cancer: a systematic review - Rizzo, Alessio; Albano, Domenico; Dondi, Francesco; Cioffi, Martina; Muoio, Barbara; Annunziata, Salvatore; Racca, Manuela; Bertagna, Francesco; Piccardo, Arnoldo; Treglia, Giorgio (Frontiers in Medicine, 2024)
Background: Several recent studies have proposed the possible application of positron emission tomography/computed tomography (PET/CT) administering radiolabelled fibroblast-activation protein (FAP) inhibitors for various forms of thyroid cancer (TC), including differentiated TC (DTC) and medullary TC (MTC). Methods: The authors conducted an extensive literature search of original studies examining the effectiveness of FAP-guided PET/CT in patients with TC. The papers included were original publications exploring the use of FAP-targeted molecular imaging in restaging metastatic DTC and MTC patients. Results: A total of 6 studies concerning the diagnostic yield of FAP-targeted PET/CT in TC (274 patients, of which 247 DTC and 27 MTC) were included in this systematic review. The included articles reported high values of FAP-targeted PET/CT detection rates in TC, ranging from 81% to 100% in different anatomical sites and overall superior to the comparative imaging method. Conclusions: Although there are promising results, the existing literature on the diagnostic accuracy of FAP-guided PET in this context is still quite limited. To thoroughly evaluate its potential significance in TC patients, it is needed to conduct prospective randomized multicentric trials.